PENGARUH SIKAP INDIVIDU, NORMA SUBJEKTIF, DAN PERSEPSI KONTROL PERILAKU TERHADAP NIAT BEPERGIAN - Ricky Husada Saputra; Olivia Barcelona Nasution (Jurnal Fokus Manajemen Bisnis, 2022)
This study aims to determine the effect of individual attitude, subjective norm, and perception of behavioral control on travel intentions during the Covid-19 pandemic. Respondents in this study were students in the Special Region of Yogyakarta who wanted to travel during the Covid-19 pandemic. Data collection techniques were carried out using questionnaires distributed through google forms and 205 respondents were obtained. The results of the study prove that individual attitude have a positive but no significant effect on travel intentions during the Covid-19 pandemic. Then, the subjective norm have a positive effect on travel intentions during the Covid-19 pandemic. Last, perception of behavioral control have a positive effect on travel intentions during the Covid-19 pandemicThis study aims to determine the effect of individual attitude, subjective norm, and perception of behavioral control on travel intentions during the Covid-19 pandemic. Respondents in this study were students in the Special Region of Yogyakarta who wanted to travel during the Covid-19 pandemic. Data collection techniques were carried out using questionnaires distributed through google forms and 205 respondents were obtained. The results of the study prove that individual attitude have a positive but no significant effect on travel intentions during the Covid-19 pandemic. Then, the subjective norm have a positive effect on travel intentions during the Covid-19 pandemic. Last, perception of behavioral control have a positive effect on travel intentions during the Covid-19 pandemic.